Central odontogenic fibroma of the maxilla - El Harti, Karima (Indian J Dent, 2015)
Central odontogenic fibroma (COF) is an uncommon tumor that accounts for 0.1% of all odontogenic tumors; it has been defined as a benign neoplasm of the jaw. Clinically, the lesion grows slowly and leads to cortical expansion. Radiologically, the most common finding is multilocular radiolucency. The lesions are associated with the crown of an unerupted molar, premolar, or incisor tooth and in some cases, with root resorption or displacement. Histologically, the lesion is characterized by mature collagen fibers and numerous fibroblasts. COF responds well to surgical enucleation with no tendency for malignancy or recurrence. We report a case of a 15-year-old female patient presented with painless swelling of the left side of the maxilla since her childhood. Radiographs revealed an expanding ill-defined radiolucency with a displacement of the adjacent tooth. The impacted tooth was pushed posteriorly. The lesion was removed surgically. There were no postoperative complications.